Relation between Chronic Periodontitis and Prevalence of Head-Neck Carcinoma in Association with Quality of Life* - Nitescu Diana-Cristala; Solomon Sorina; Ursarescu Irina; Martu Ioana; Martu Cristian; Martu Silvia (Balkan Stomatological Society, 2015)
Background and Aim: Substantial evidence supports an association between chronic infections/inflammation, and cancer. The aim of this study was to assess the effect of chronic periodontitis on head and neck squamous-cell carcinoma (HNSCC).